Cristais anidros das bases do ADN são semicondutores de Gap largo - Maia Júnior, Francisco Franciné (2011)
Guanine (G), adenine (A), cytosine (C), and thymine (T) nucleotide bases are the essential building blocks of DNA (deoxyribonucleic acid), which contains the genetic information used to build living cells. DNA strands are also promising candidates to fabricate molecular nanodevices, since they are stable polymers easy to replicate. Despite the early suggestion of the possibility of using DNA as a nanoscale conductor almost ten years after the elucidation of its helical structure, charge carrier transport through DNA-based structures is still a matter of debate. Here, we present the structural, electronic and optical properties of anhydrous crystals of DNA nucleobases found after DFT (Density Functional Theory) calculations, as well as experimental measurements of optical absorption for powders of these crystals. Experimental measurements of the UV absorption spectra for the anhydrous crystals were carried out on these pellets using a Varian Cary 5000 UV-visible NIR spectrophotometer. The absorption spectrum of the samples was recorded in the wavelength range between 200 and 800 nm (50000-12500 cm-1). The computational simulations of the present work were performed using the CASTEP code, which is based in the DFT approach. The Local Density Approximation (LDA) exchange-correlation potential developed by Ceperley and Alder and parametrized by Perdew and Zunger was adopted as well. With respect to our choice of functional, a note of caution must be made: in anhydrous DNA bases crystals, van der Waals interactions along the molecular stacking axis and hydrogen bonding between molecules in the same stacking plane are relevant to explain their structural features, and it is well known that pure DFT methods are unable to give a good description of dispersive forces. Besides, the LDA approximation is not the best option to provide an accurate account of hydrogen bonds. However, some DFT studies of layered crystals such as graphite as well as guanine hydrated crystals have shown that the LDA gives reasonable values for atomic distances, notwithstanding the limitations of this functional. This and the relatively low cost of LDA computations have motivated us to its adoption instead of more sophisticated (and computationally expensive) means. Guanine and cytosine (adenine and thymine) anhydrous crystals are predicted from the DFT simulations to be direct (indirect) band gap semiconductors, with values 2.68 eV and 3.30 eV (2.83 eV and 3.32 eV), respectively, while the experimentally estimated band gaps we have measured are 3.7 eV and 3.8 eV (3.5 eV and 4.0 eV), in the same order. Our LDA figures for the energy gaps are smaller than experimental values, as expected, and the gaps estimated from the optical absorption measurements presented in this work are in general smaller than experimental data available in the literature (except for guanine). The LDA ordering of increasing band gaps is G < A < C < T, while the ordering of gaps obtained experimentally is not settled: our work finds (from optical absorption measurements) A < G < C < T in contrast with the X-ray measurements, that indicate the energy gap sequence G < C < A < T. For electrons and holes moving along selected hydrogen bonds (parallel to the molecular plane of a given nucleobase), effective masses are in general large, exception made to thymine. When the same electrons move along the pi-stacking axis, however, effective masses stay between 4.0 and 6.3 free electron masses (m0), which suggests that stackings of nucleobases behave like wide gap semiconductors for electrons. The perpendicular transport of holes is also favored for nucleobase stackings without thymine. Finally, the complex dielectric function was calculated for each anydrous DNA base crystal, and a very pronounced anisotropy was observed for polarized incident light in the cases of guanine, adenine, and thymine, but not for cytosine.